Upaya guru memanfaatkan perpustakaan sekolah sebagai sumber belajar di Sekolah Dasar Negeri Tosanan Ponorogo - Riyanto Riyanto; Muh. Tajab; Moh. Rifan; Wuryono Wuryono; Nursiah Nursiah; Krista Alifa Setyaningrum; M. Habib Izazur Ridhwan (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. The aim of the paper is to understand the efforts of Islamic education teachers in utilizing the library as one of the school's facilities and infrastructure, at State Elementary School of Tosanan Ponorogo by using the approach of the Association for Education Communication Technology (AECT). Data Collection Methods. This was a qualitative descriptive with by observations and, structured interviews. Data Analysis. The interview data was transcribed for analysis. Results and Discussion. The efforts showing by teacher’s to utilize the school library as a learning resource are shown by improving their quality. These Include how to absorb information from the library as teaching, to increase the intensity of visits to the library, to increase the collection/number of books and to make the best use of the existing library facilities. Conclusions and Recommendations. The library at State Elementary School of Tosanan Ponorogo has not been maximally utilized as a learning resource in every lesson. This library should increase the number of books, support facilities for users and manage library base on standards. For further research it is hoped that it can be expanded, so that it is not limited to Islamic religious education teachers but to teachers of other subjects.